Long-term follow up of varus osteotomy of the femur in patients with Perthes` disease in Erbil City - Mohammed Ridha, Zainab Abdulwahab (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: Perthes disease is a condition in which a self-limiting avascular problem affects the capital epiphysis of the femur with a variable course and outcomes. There are patients who definitely benefit from different treatment courses, either surgical or non-surgical, but better with surgical. This study aimed is to determine the outcome of varus derotational osteotomy procedure in the management of Perthes disease. Methods: In this retrospective study, which was conducted in the orthopedic department of Erbil teaching hospital, 21 patients (22 hips) with Perthes` disease were enrolled over the period of 10- years, from 2008 to 2018. Varus derotational osteotomy to proximal femur was done for all 22 hips affected by Perthes disease in different radiological stages. Results: Among the patients, 81.0% were males and right side of the hip was the most predominant (52.4%) affected side. Partial limitation of hip movements with +ve Trendelenburg sign were the main clinical findings (52.4%), especially among those aged ≤8 years, males and left side affected patients (54.5%, 72.7%, and 63.6%, respectively). Subluxation and metaphyseal resorption were the main radiological findings of the head of the femur (36.4% and 31.8%, respectively). Radiological stages of the patients mainly showed early fragmentation, late fragmentation, and early healing stages (27.3%, 27.3%, and 22.7%, respectively). Postoperatively, 59.0% of the patients had a good prognosis (Stulberg grades 1 and 2), while 31.9% had a fair prognosis. Those aged ≤8 years had a better prognosis with a significant statistical association between Stulberg classification and those with lateral pillar B & B/C and early three radiological stages (P = 0.01 and 0.005). Conclusion: Open wedge varus femoral osteotomy is the treatment of choice and gives good results. The strongest predictor of outcomes is Stulberg classification in relation to age, lateral pillar classification, and preoperative radiological stages of the disease.